A non–GPCR-binding partner interacts with a novel surface on β-arrestin1 to mediate GPCR signaling - Zhuo, Ya (J Biol Chem, 2020)
The multifaceted adaptor protein β-arr1 (β-arrestin1) promotes activation of focal adhesion kinase (FAK) by the chemokine receptor CXCR4, facilitating chemotaxis. This function of β-arr1 requires the assistance of the adaptor protein STAM1 (signal-transducing adaptor molecule 1) because disruption of the interaction between STAM1 and β-arr1 reduces CXCR4-mediated activation of FAK and chemotaxis. To begin to understand the mechanism by which β-arr1 together with STAM1 activates FAK, we used site-directed spin-labeling EPR spectroscopy-based studies coupled with bioluminescence resonance energy transfer–based cellular studies to show that STAM1 is recruited to activated β-arr1 by binding to a novel surface on β-arr1 at the base of the finger loop, at a site that is distinct from the receptor-binding site. Expression of a STAM1-deficient binding β-arr1 mutant that is still able to bind to CXCR4 significantly reduced CXCL12-induced activation of FAK but had no impact on ERK-1/2 activation. We provide evidence of a novel surface at the base of the finger loop that dictates non-GPCR interactions specifying β-arrestin–dependent signaling by a GPCR. This surface might represent a previously unidentified switch region that engages with effector molecules to drive β-arrestin signaling.